1982
DOI: 10.1007/bf00254295
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of glomerular basement membrane in type 1 (insulin-dependent) diabetic children

Abstract: Immunoelectrophoresis of glomerular basement membrane antigens in the urine of 20 Type 1 (insulin-dependent) diabetic and 10 healthy children was performed. In 10 of the diabetic children, there was altered alpha-1-mobility, while the other diabetic and normal children showed alpha-2-mobility. After incubation with glucose, glomerular basement membrane antigens in the urine of healthy children showed alpha-1-mobility. Isolated human kidney glomerular basement membrane split products obtained by proteolytic deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Cohen et al [6] reported that increased glycosylation of G B M collagen from rats with STZ-induced diabetes may alter structure-function relation ships o f the capillary filtration barrier [6]. Schober et al [18] reported marked glycosylation o f G B M in insulindependent diabetic children. Recently, Nishimura et al [19] and Dobashi [20] reported high levels of lipid perox ide in retina, kidneys and plasma in STZ-induced dia betic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al [6] reported that increased glycosylation of G B M collagen from rats with STZ-induced diabetes may alter structure-function relation ships o f the capillary filtration barrier [6]. Schober et al [18] reported marked glycosylation o f G B M in insulindependent diabetic children. Recently, Nishimura et al [19] and Dobashi [20] reported high levels of lipid perox ide in retina, kidneys and plasma in STZ-induced dia betic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have not dissociated the effects of glomerular hypertension and hyperperfusion from those of chronic hyperglycemia per se (20)(21)(22). In the present study, glomerular hemodynamic function was deliberately varied in rats with streptozotocin (STZ)-induced diabetes while stable moderate hyperglycemia was maintained by daily exogenous insulin.…”
Section: Introductionmentioning
confidence: 94%
“…Glomerular morphologic changes resembling those seen in diabetes have been associated with increases in capillary pressures and flows in other experimental forms of renal disease, including ablation ofrenal mass (11-13), high-protein diet (14), and some models of hypertension (15, 16). Furthermore, the extent of glomerular lesions in diabetic rats can be enhanced by maneuvers known to increase glomerular capillary pressures and flows, such as contralateral renal arterial clipping (17), ablation of the contralateral kidney (18), or high-protein feeding (19).Studies to date have not dissociated the effects of glomerular hypertension and hyperperfusion from those of chronic hyperglycemia per se (20)(21)(22). In the present study, glomerular hemodynamic function was deliberately varied in rats with streptozotocin (STZ)-induced diabetes while stable moderate hyperglycemia was maintained by daily exogenous insulin.…”
mentioning
confidence: 99%
“…Schober et al [3] reported marked glycosylation of GBM in type I (in sulin-dependent) diabetic children. We reported an in crease of glycosylated proteins in renal tissues obtained from patients with non-insulin-dependent diabetes melli tus (NIDDM) with nephropathy [4], However, the patho genesis of renal involvement in patients with diabetes has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%